Explorer les effets de la langue comme obstacle à l’accès aux soins, à l’utilisation des services et au bien-être pour les familles anglophones du Québec - McGill Department of Educational and Counselling Psychology; CareLab (2022)
La langue a été nommée comme obstacle à l’accès et à l’utilisation des soins de santé pour les anglophones du Québec et pour une multitude d’autres minorités linguistiques partout dans le monde. Plus précisément, ces obstacles se manifestent par la difficulté d’accéder à un professionnel de la santé, par exemple pour prendre un rendez-vous dans la langue de son choix, le manque de choix quant aux traitements et services nécessaires, la difficulté à comprendre le plan de traitement et les résultats d’examens et le manque de services dans la langue de son choix lorsqu’on est orienté vers un spécialiste de la santé.

Consensus on Language Issues in Quebec - Quebec Community Groups Network (QCGN); Association for Canadian Studies (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Partners in Health - Centre for Access to Services in English (CASE) (2022)

2018–2021 Health and Social Services Bursary Program Portrait - Dialogue McGill (2022)
Created by Dialogue McGill in 2011 as a retention initiative, the Health and Social Services Bursary Program provides bursaries to students pursuing studies in health care and psychosocial services who have committed to practice in their field in their home region upon completion of their studies. The bursaries are coordinated locally by the English- speaking Community Networks in different Quebec regions and are designed to respond to regional and local priorities for access to services in English by retention of these graduates in their region of origin.

Le modèle de liaison communautaire : Améliorer l'accès aux services de santé et aux services sociaux pour les communautés d'expression anglaise du Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2022)
Ce rapport explore le rôle du travail de liaison communautaire dans l'amélioration de la santé et du bien-être des personnes et des communautés qui font face à des obstacles dans leur accès aux services de santé publics. Il s'intéresse plus particulièrement au modèle de liaison du CHSSN, qui constitue une réponse communautaire prometteuse pour réduire les obstacles linguistiques et culturels auxquels se heurtent les communautés d’expression anglaise du Québec.
Keywords: Official Language Minority Community (OLMC)

The Community Liaison Model : Improving Access to Health and Social Services to Quebec's English-speaking Communities - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2022)
This report explores the role of community liaison work in improving the health and wellbeing of individuals and communities who face barriers in their access to public healthcare services. Of specific focus is the CHSSN liaison model as a promising community-based response to reducing the linguistic and cultural barriers experienced by Quebec’s Englishspeaking communities.
Keywords: Official Language Minority Community (OLMC)

Understanding the Long-term Care Experience of Official Language Minorities in Canada: An Environmental Scan - Hsu, Amy T.; Ménard, Alixe; Scott, Mary (2022)
Members of minority and racialized communities across Canada commonly experience disparities in health and healthcare. In the context of the COVID-19 pandemic, minority and racialized individuals have been found to report poorer health outcomes and added barriers to healthcare access. While there is growing understanding of the impact of COVID-19 on individuals who live and work in residential long-term care (LTC) homes and other congregate care settings, little attention has been directed at examining inequities in the care experience and care-related outcomes that equity-seeking groups, including Official Language Minority Communities (OLMC), face within LTC. It’s clear that there is a need for systemic change within LTC; the pandemic, especially in its first two waves, highlighted several pre-existing issues within this sector. To ensure high-quality and equitable care for all aging Canadians, these system-level changes must be informed by evidence.
Keywords: Official Language Minority Community (OLMC)

Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada : état des lieux - Hsu, Dre. Amy T; Ménard, Alixe; Scott, Mary (2022)
Les membres des communautés racisées et en situation minoritaire du Canada vivent souvent des disparités en matière de santé et de soins de santé. Dans le contexte de la pandémie de COVID-19, on a constaté que les personnes membres d’une minorité et les personnes racisées signalaient de moins bons résultats de santé et des barrières supplémentaires à l’accès aux soins de santé. Bien que l’on comprenne de plus en plus l’incidence de la COVID-19 sur les personnes vivant et travaillant dans des établissements de soins de longue durée (SLD) et dans d’autres établissements de soins collectifs, on a porté peu d’attention à l’examen des inégalités dans l’expérience des soins et des résultats liés aux soins auxquels font face les groupes en quête d’équité, y compris les communautés de langue officielle en situation minoritaire (CLOSM). Il est clair qu’il faut apporter des changements systémiques au sein du secteur des SLD; la pandémie, surtout au cours de ses deux premières vagues, a mis en lumière plusieurs problèmes préexistants dans ce secteur. Pour assurer des soins de grande qualité et équitables pour tous les Canadien(ne)s âgés, ces changements au niveau du système doivent être fondés sur des données probantes.
Keywords: Official Language Minority Community (OLMC)

Committee Examines Obligations of Professionals to Provide Documentation in French - Quebec Community Groups Network (QCGN) (2022)

La commission examine l’obligation des professionnels de fournir leur documentation en français - Quebec Community Groups Network (QCGN) (2022)

Quietly Adopted Regulation Could Hurt Quality of Health Care for English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2022)

Un réglement adopté en catimini pourrait nuire à la qualité des soins de santé des Québécois d'expression anglaise - Quebec Community Groups Network (QCGN) (2022)

Améliorer la santé et le bien-être des aînés d’expression anglaise vivants dans les Laurentides au Québec - Helou, Rola; Finch, Lois; Richardson, Mary (4Korners, 2022)
La présente évaluation des besoins a été réalisée à la demande du Réseau communautaire des Laurentides 4Korners, un organisme caritatif canadien enregistré qui a été fondé en 2005 dans le but de faire connaître aux citoyens des Laurentides les programmes et les services qui répondent à leurs besoins dans un environnement sécuritaire et inclusif. Elle a pour objectif de déterminer les besoins de la population âgée d’expression anglaise des Laurentides et de vérifier si ces besoins sont présentement satisfaits. Cette évaluation a été menée par le Conseil scolaire des Premières Nations en éducation des adultes, en collaboration avec la firme de consultants S.O.A.R. Solutions. Les travaux ont été réalisés sous la supervision du Comité d’évaluation des besoins des aînés (SNAC), lequel est composé de membres du personnel de 4Korners, du Elders’ Community Worker du Centre de santé Kanesatake, de bénévoles et de consultants en projets du Conseil scolaire des Premières Nations en éducation des adultes.

Improving the Health and Well-being of English-speaking Seniors in the Laurentians, Québec : A Needs Assessment - Helou, Rola; Finch, Lois; Richardson, Mary (4Korners, 2022)
This needs assessment was commissioned by the 4Korners Laurentian Community Network, a registered Canadian charitable organization founded in 2005, which connects individuals of the Laurentians with programs and services to meet their needs in a secure and inclusive environment. The objective was to identify the needs of the aging English-speaking population in the Laurentians and to determine if they are currently being met. The First Nations Adult Education School Council conducted the assessment in partnership with S.O.A.R. Solutions, a consulting firm. The work was overseen by a committee (the Seniors’ Needs Assessment Committee, SNAC), made up of 4Korners employees, volunteers, the Elders’ Community Worker from the Kanesatake Health Center and project consultants from the First Nations Adult Education School Council.

CHSSN Community Netlink - Community Health and Social Services Network (CHSSN) (2022)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2022)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2022)

Community NetLink - Community Health and Social Services Network (CHSSN) (2022)

Sondage Youth Pulse Check : Principales conclusions - Community Health and Social Services Network (CHSSN) (2022)

Youth Pulse Check Survey : Key Findings - Community Health and Social Services Network (CHSSN) (2022)

Lunch & Learn : Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada: un état des lieux / Understanding the Long-Term Care Experience of Official Language Minorities in Canada : An Environmental Scan - Ménard, Alixe; Scott, Mary; Hsu, Amy (2022)

Sondage Youth Pulse Check : Rapport des résultats du sondage - Nigam, Sunita (Community Health and Social Services Network (CHSSN), 2022)
This document outlines the most important findings of the Youth Pulse Check, a mental health survey filled out by 456 English-speaking youth between the ages of 18-29 from 14 regions across the province of Quebec. Although 90% of respondents said they struggled at least somewhat often with their mental wellbeing and 81% of respondents, said that the COVID-19 pandemic has increased their struggles to feel well at a level 3 or more on a scale of 1 to 5, the survey revealed that many English-speaking youth feel there are significant gaps and barriers in accessing mental health services in their region. If many youth reported having sought out help in the past without success—meeting with barriers such as long wait lists, the prohibitive costs of mental health support, or the unavailability of services in English— other youth reported not having sought out help because of a lack of information about services to which they might turn.

Youth Pulse Check : Survey Results Report - Nigam, Sunita (Community Health and Social Services Network (CHSSN), 2022)
This document outlines the most important findings of the Youth Pulse Check, a mental health survey filled out by 456 English-speaking youth between the ages of 18-29 from 14 regions across the province of Quebec. Although 90% of respondents said they struggled at least somewhat often with their mental wellbeing and 81% of respondents, said that the COVID-19 pandemic has increased their struggles to feel well at a level 3 or more on a scale of 1 to 5, the survey revealed that many English-speaking youth feel there are significant gaps and barriers in accessing mental health services in their region. If many youth reported having sought out help in the past without success—meeting with barriers such as long wait lists, the prohibitive costs of mental health support, or the unavailability of services in English— other youth reported not having sought out help because of a lack of information about services to which they might turn.

English : an Asset! - Réseau de l’est de l’île pour les services en anglais (REISA) (2022)